Impact of Comorbidities on Prostate Cancer Stage at Diagnosis in Florida. (July 2016) - Xiao, Hong; Tan, Fei; Goovaerts, Pierre; Adunlin, Georges; Ali, Askal Ayalew; Gwede, Clement K.; Huang, Youjie
To examine the association of major types of comorbidity with late-stage prostate cancer, a random sample of 11, 083 men diagnosed with prostate cancer during 2002-2007 was taken from the Florida Cancer Data System. Individual-level covariates included demographics, primary insurance payer, and comorbidity following the Elixhauser Index. Socioeconomic variables were extracted from Census 2000 data and merged to the individual level data. Provider-to-case ratio at county level was alsocomputed. Multilevel logistic regression was used to assess associations between these factors and late-stage diagnosis of prostate cancer. Higher odds of late-stage diagnosis was significantly related to presence of comorbidities, being unmarried, current smoker, uninsured, and diagnosed in not-for-profit hospitals. The study reported that the presence of certain comorbidities, specifically 10 out of the 45, was associated with late-stage prostate cancer diagnosis. Eight out of 10 significant comorbid conditions were associated with greater risk of being diagnosed at late-stage prostate cancer. On the other hand, men who had chronic pulmonary disease, and solid tumor without metastasis, were less likely to be diagnosed with late-stage prostate cancer. Late-stage diagnosis was associated with comorbidity, which is often associated with increased health care utilization. The association of comorbidity with late-stage prostate cancer diagnosis suggests that individuals with significant comorbidity should be offered routine screening for prostate cancer rather than focusing only on managing symptomatic health problems.